2020
DOI: 10.1016/j.jmmm.2019.166142
|View full text |Cite
|
Sign up to set email alerts
|

Nanopatterned hard/soft bilayer magnetic antidot arrays with long-range periodicity

Abstract: A top-down approach using focused ion beam has been employed to fabricate Co/Permalloy hard-soft bilayer magnetic antidot arrays. These nanopatterned films are studied with particular emphasis on magnetic coercivity. The antidots have a diameter of 40 nm and the studied antidot symmetries are square and hexagonal. A dependence of magnetic coercivity on the relative thicknesses of the magnetically hard (Co) and soft (Permalloy) layers is found; increasing Permalloy thickness results in lower magnetic coercivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…1). The sizes considered in our simulations are similar to some experimentally studied arrays 25,26,41,60,64,65 .…”
Section: Micromagnetic Simulationsmentioning
confidence: 62%
See 1 more Smart Citation
“…1). The sizes considered in our simulations are similar to some experimentally studied arrays 25,26,41,60,64,65 .…”
Section: Micromagnetic Simulationsmentioning
confidence: 62%
“…From the experimental point of view there are several techniques for obtaining magnetic antidot arrays such as e-beam 2 , 17 , UV 18 and colloidal 19 lithography, porous anodic alumina 20 , 21 , block copolymer templates 22 , nanochannel glass 23 and focused ion beam (FIB) patterning 24 26 , among others. Regarding the features that antidots possess, it has been widely reported that static properties such as remanence 27 , coercivity 27 , 28 , and the easy-axis magnetic anisotropy 28 31 , can be controlled by modifying the hole size, the distance between them, and the material used to fabricate the array.…”
Section: Introductionmentioning
confidence: 99%
“…In a conventional 2D antidot matrix, the reversal process is only induced by the coherent rotation of its magnetic moments where its magnetic domain aligns along the field direction. [26,28] The difference in behavior is attributed to the extra HGS layer over the conventional antidot matrix, which forms a 3D magnetic lattice in the same material, demonstrating how one can design 3D structures to tailor properties of magnetic nanostructures.…”
Section: Magnetization Reversal Studymentioning
confidence: 99%
“…In particular, the shape, size, lateral dimensions, choice of materials, and lattice geometries are engineerable variables that allow a fine tuning of the antidot lattice properties. Specifically, changes in geometrical parameters result in a change in the strength and profile of the stray fields [10] across the antidots, which leads to different pinning and motion of the domain walls through the lattice [11][12][13]; whereas changes in the thin film composition and/or thicknesses lead to different coupling strengths between magnetic domains [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…To date, antidot thin films have been studied targeting specific scientific advances in their properties and functionalities, such as engineering their perpendicular anisotropy through material properties tuning [16,[18][19][20]; combining soft and hard magnetic materials in multilayered antidot lattices to engineer their coercivity [12,13,21]; studying the propagation of magnons and spin waves through the antidot lattices [15,17,[22][23][24][25][26][27][28][29][30][31][32][33]; nucleating and propagating skyrmions through the lattices [34]; enabling the antidot arrays as platforms for spintronic applications [13,19]; enabling the antidot arrays for use as monolithic microwave band-pass filters [25] or high density storage ferroelectric memories [35]. Nonetheless, there is still room for improvement in terms of engineering the properties of the magnetic materials from which the antidots are made, as this crucially affects their properties, and, therefore, their target applications.…”
Section: Introductionmentioning
confidence: 99%